Multiple PDE3A modulators act as molecular glues promoting PDE3A-SLFN12 interaction and induce SLFN12 dephosphorylation and cell death. Issue 6 (16th June 2022) - Yan, Bo; Ding, Zhangcheng; Zhang, Wenbin; Cai, Gaihong; Han, Hui; Ma, Yan; Cao, Yang; Wang, Jiawen; Chen, She; Ai, Youwei
Summary: The canonical function of phosphodiesterase 3A (PDE3A) is to hydrolyze the phosphodiester bonds in second messenger molecules, such as cyclic AMP (cAMP) and cyclic guanosine monophosphate (cGMP). Recently, a phosphodiesterase-activity-independent role for PDE3A was reported. In this noncanonical function, PDE3A physically interacts with Schlafen 12 (SLFN12) upon treatment of cells with cytotoxic PDE3A modulators. Here, we confirmed that the cytotoxic PDE3A modulators act as molecular glues to initiate the association of PDE3A and SLFN12. The PDE3A-SLFN12 interaction increases the protein stability of SLFN12 located in the cytoplasm, while at the same time also inducing SLFN12 dephosphorylation (including serines 368 and 573). Mutational analysis demonstrates that dephosphorylation is required for cell death induced by cytotoxic PDE3A modulators. Finally, we found that dephosphorylation promoted the rRNA RNase activity of SLFN12 and show that this nucleolytic activity is essential for SLFN12's cell-death-inducing function. Thus, our study deepens the understanding of the biochemical mechanisms underlying SLFN12-mediated cell death. Graphical abstract: Highlights: Multiple cytotoxic PDE3A modulators act as molecular glues PDE3A-SLFN12 interaction reduces the phosphorylation of SLFN12 Dephosphorylation of SLFN12 increases SLFN12's RNase activity Abstract : Yan et al. find that multiple PDE3A modulators act as molecular glues that promote PDE3A-SLFN12 interaction, which results in dephosphorylation of SLFN12. Mutational analyses demonstrate that dephosphorylation of SLFN12 is required for SLFN12's cell-death-inducing function, which is mediated through SLFN12's RNase activity against rRNAs.